2016
DOI: 10.1080/1547691x.2016.1194917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of administration timing of postchemotherapy granulocyte colony-stimulating factor on host-immune cell recovery and CD8+ T-cell response

Abstract: Granulocyte colony-stimulating factor (G-CSF), a hematopoietic growth factor, is a standard supportive therapy given during cancer treatment. It induces acceleration in neutrophil recovery through stimulation of mobilization of hematopoietic progenitors. Given that the latter is also induced by chemotherapy itself, the timing of administration of G-CSF post-chemotherapy might impact the resultant overall effects. The present study aimed to determine the optimal timing of G-CSF post chemotherapy to exert its op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…However, again, effects of the G-CSF were short-lived. In this study G-CSF showed immune stimulating effect resulted in ameliorating effect on leucocytes count in bone marrow and spleen, Also increasing the lymphocytes count, relative and absolute numbers of neutrophils These results were consistent with those from (Salem et al, 2016), (Demetri and Griffin 1991) who noted G-CSF administration induced increases in WBC counts by acting as a potent hematopoietic growth factor.…”
Section: Effect Of Sp Treatment On Alt and Ast Activitiessupporting
confidence: 92%
See 3 more Smart Citations
“…However, again, effects of the G-CSF were short-lived. In this study G-CSF showed immune stimulating effect resulted in ameliorating effect on leucocytes count in bone marrow and spleen, Also increasing the lymphocytes count, relative and absolute numbers of neutrophils These results were consistent with those from (Salem et al, 2016), (Demetri and Griffin 1991) who noted G-CSF administration induced increases in WBC counts by acting as a potent hematopoietic growth factor.…”
Section: Effect Of Sp Treatment On Alt and Ast Activitiessupporting
confidence: 92%
“…injection of PBS (Phosphate buffer saline) as control, once i.p. injection of CTX (4 mg/mouse) for induction of leucopenia, subcutaneous (s.c.) injection two days after CTX injection (the time point where leucopenia that occurred (Salem et al, 2016) of 5 µg/mouse G-CSF (Neupogen, CA, USA) daily for 5 consecutive days. To test the impact of SP on leucopenia, mice were treated for 7 consecutive days orally using stomach gavage of 500 mg/mouse starting on the day of CTX injection.…”
Section: Treatment Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from this study suggest that harnessing neutrophil cytotoxicity in bone by regulating neutrophil maturation and mobilization could prevent PCa growth in bone. For example, granulocyte colony-stimulating factor (G-CSF) is a primary regulator of neutrophil proliferation and differentiation and is often given to cancer patients to replenish the neutrophil population after chemotherapy-related neutropenia [43]. G-CSF mimetics are currently in clinical trial in combination with chemotherapy and could be considered for treatment of BM-PCa [44].…”
Section: Discussionmentioning
confidence: 99%